Aspects of Intermediality in the Poems of Alfonsas Nyka-Niliūnas: A Case of a Dialogue between Poetry and Art - Andrulytė, Monika (Respectus Philologicus, 2019)
[full article and abstract in Lithuanian; abstract in English]The article analyses a dialogue of poetry with art in five Alfonsas Nyka-Niliūnas’ poems. It has been selected to apply an intermedial analysis, which provides analytical tools assisting in studying the parameters of a dialogue with art. The most important thing is the conception of ekphrasis predicting the gesture of media change – expressing visual work in words. It has been based on the typology of Laura M. Sager Eidt’s ekphrases, which allows seeing that the studied poems of Nyka-Niliūnas are dominated by a dramatic ekphrasis, the essential feature of which is an intensive autoreflection. The article studies in deep the particularity of an intermedial dialogue: it is considered on which basis the poetry of Nyka-Niliūnas is associated with artworks, how this dialogue is given prominence and what meaning growth is seen. It is analysed how art intertexts in the poems establish new meanings, and the aspect of linguistic visualisation is discussed. It has been seen that the strategy of intermedial reading is mostly formed in the titles of poems, which are introduced to the dialogue with the situation of visual media. The art quotations in the analysed texts perform different functions – activate the subjects of representation problems and representation variability, help in creating tension between visualisation and acoustics and strengthen the ideas of philosophy of existence.
Keywords: Alfonsas Nyka-Niliūnas; intermediality; art quotations; ekphrasis